Case Report: Two Cases of Soft-Tissue Sarcomas: High TMB as a Potential Predictive Biomarker for Anlotinib Combined With Toripalimab Therapy - Li, Yong; Liu, Yihong; Qu, Yanchun; Chen, Xian; Qu, Xin; Ye, Yongsong; Du, Xiaohua; Cheng, Ying; Xu, Mian; Zhang, Haibo (Frontiers in Immunology, 2022)
Soft-tissue sarcomas (STS), with over 100 different histologic subtypes, are rare tumors that account for 1% of all adult malignancies. Immune checkpoint inhibitors (ICIs) display certain benefits in some subtypes, especially in undifferentiated pleomorphic sarcoma (UPS), alveolar soft part sarcoma (ASPS), and leiomyosarcoma (LMS). However, efficacy is difficult to predict. High tumor mutational burden (TMB-H) and programmed death-ligand 1 (PD-L1) expression are the strongest features associated with the efficacy of immunotherapy, although they are rarely found in STS patients. Until now, whether or not PD-L1 expression and TMB are related to the efficacy of immunotherapy has not been determined. In this study, we report data obtained from two STS patients, one ASPS and one UPS with a high TMB, that benefited from anlotinib combined with toripalimab following resistance to anlotinib monotherapy. A 26 year-old female patient was diagnosed with ASPS. PD-L1 was negative. Next generation sequencing (NSG) revealed ASPSCR1-TFE3 fusion and TMB-H. Following eight months of anlotinib monotherapy, the patient's disease progressed but continued to benefit from subsequent use of anlotinib combined with toripalimab. Another 63 year-old male patient was diagnosed with UPS. PD-L1 was positive and NGS revealed TMB-H. Following 19 months of anlotinib monotherapy, the patient's disease progressed but continued to benefit from subsequent use of anlotinib combined with toripalimab. The results presented are the first to report the relationship between TMB and the efficacy of immunotherapy in STS. Based on our results, we concluded that anlotinib combined with toripalimab is effective for the treatment of some advanced ASPS or UPS. TMB may be a potential predictive biomarker for ICI treatment and deserves additional study.